Design, synthesis and characterization of novel rhenium(V) and technetium(V) complexes as potential radiopharmaceuticals - Hlabela, Patrick Simon (Rhodes University, Faculty of Science, Department of Chemistry, 2001)
A number of bidentate N, N-diethyl-N' -(R ')benzoylthiourea ligands (where R' = H,CH₃,CI,OCH₃ and N0₂) have been synthesized, as well as the three Re(V) precursor complexes, ReOCl₃(PPh₃)₂,[ReO₂(py)₄]CI and [n-Bu₄N] [ReOCI₄J. The reaction of N,N-diethyl-N'-benzoylthiourea (LH) with these three metal precursor complexes in methanol in the presence of a base gave a novel mixed-ligand complex bis(N,N-diethyl-N'-benzoylthioureato)methoxyoxorhenium(V), [ReO(L)₂(OMe)] (1). In the absence of a base and under an inert atmosphere, the reaction between [n-Bu₄N][ReOCI₄] and LH yielded bis(N,N-diethyl-N'-benzoylthioureato)chlorooxorhenium(V), [ReO(L)₂CI] (lb). The reaction of LH with [ReO₂(py)₄]CI in ethanol and iso-propanol in the presence of sodium acetate gave the novel mixed ligand complexes bis(N,N-diethyl-N'benzoylthioureato) ethoxyoxorhenium(V), [ReO(L)₂(OEt)] (6) and bis(N,N-diethyl-N'benzoylthioureato)(iso-propoxy)oxorhenium(V), [ReO(L)₂(OiPr)] (7), respectively. An oxygen bridged dirhenium complex, [(L)₂0Re-O-ReO(L)₂] (15) was obtained when the reaction was carried out in acetonitrile. A series of mixed ligand Re(V)-oxo complexes using N, N-diethyl-Nʾ-(R' )benzoylthiourea (LR'),N,N-morpholino-N' -(R')benzoylthiourea (morph-LR') and 8-(N-(R')benzoylthiocarbamoyl)-1,4-dioxa-8-azaspiro[4.5]decane ligands (spiro-LR') (where R' = H,CH₃,CI, OCH₃ and N0₂) ((1)(14) have been prepared by the reaction of [ReO₂(py)₄]CI and the ligand in the presence of sodium acetate in methanol. The solution state chemistry of these complexes has shown that complexes(1)-(14) (with the exception of (1b)) undergo dimerization in solution to give complex (15) in the presence of water. Preliminary ¹H NMR kinetics studies of the dimerization of (1), (6) and (7) to (15) have shown that the rate of dimerization decreases in the order (7) > (6) > (1). The rate of dimerization has also been compared for complexes (1), [ReO(morph-L)₂(OMe)] (8) and [ReO(spiro-L)₂(OMe)] (13) and the rate of dimerization was found to be fastest for (13). The crystal structures of (1), [ReO(LN0₂)₂(OMe)] (4), (6) and (15) have been determined. The Re(V)-oxo complexes (1), (4) and (6) have a slightly distorted octahedral geometry with the two acylthiourea ligands binding in a cis arrangement in the equatorial plane of the octahedron. The alkoxy and oxo ligands occupy the axial positions and are situated trans to each other. The crystal and molecular structure of complex (15), consist of two slightly distorted octahedral [ReO(L)₂] moieties bridged by an oxygen atom with a Re-O-Re bond angle of 175.2(2)°. The preliminary studies done in the present study have indicated that the complexation chemistry of technetium(V) with the N,N-diethyl-benzoylthiourea is different to that of rhenium (V). The reaction between [n-BuN₄][TcOCl₄] and N,N-diethyl-N'-benzoylthiourea yielded the square pyramidal cationic complex [TcO(L)₂]Cl. By contrast the octahedral methoxy complex [ReO(L )₂( OMe)] was obtained when the analogous Re(V)-oxo precursor, [n-Bu₄N] [ReOCI₄], was reacted with N,N-diethyl-N'-benzoylthiourea under the same reaction conditions.
Keywords: Radiopharmaceuticals; Rhenium; Technetium